Gambaran Korupsi Waktu terhadap Mahasiswa Prodi MIK Asrama di Stikes Santa Elisabeth Medan - Monika Simanjuntak (Yayasan Literasi Sains Indonesia, 2024)
Basically, corruption is not only about money, possessions or riches, but also about time. Time is the most basic thing in an act of corruption. Many people are not aware of this. Children, teenagers, adults and even old people commit acts of time corruption. Time corruption is serious problems in everyday life. By appreciating time and using it efficiently, we can increase productivity and achieve the goals we want. This article aims to analyze time corruption in a social context. This research uses observation and interview methods to obtain accurate and relevant data. The research results show that time corruption can occur in various sectors. Factors that influence time corruption include a lack of personal discipline, a habitual tendency to procrastinate, a lack of good time planning, and an addiction to technology and social medicine. The implication of this research is the need for awareness in overcoming time corruption in order to achieve better efficiency and productivity in everyday life.